Organic Horticulture in Northeast India: Strategies and Prospects - Avasthe, Ravikant; Patel, V B (Indian Horticulture, 2024)
Northeast India includes eight states viz., Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim and Tripura, occupy 7.7% of India’s total geographic area and nurture nearly 50% of the biodiversity in the country of which about 32% is endemic. Mostly indigenous farming practices are followed in Northeast which are predominantly organic in nature and depend on the indigenous technical knowledge systems prevalent in the region for centuries. Agro-climatic conditions of the region are rainfed and most conducive for organic farming. The region is bestowed with diversity of numerous fruits, vegetables, flowers, spices, medicinal plants and a vast array of indigenous crops. Diversity in horticultural crops embraces the potential to strengthen the economy and ecology of the region through the adoption of organic horticulture by NPOP Guidelines based farm production and wild collection either as commodities or value-added products. Sikkim was declared as the first fully organic state of the country in 2016 and all the other Northeastern states aim to shift towards organic farming.